GERAKAN RADIKALISME ISLAM DI INDONESIA - Nuraida Nuraida (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
The time of reformation. It's just that since the Reformation movement was radicalization grow more rapidly. At least two factors causing the emergence of Islamic radicalism in Indonesia. First, the internal factors. In this context, the emergence of the reaction of the Muslims because they see religion has been manipulated by political interests and power, used religion as a justification for the launch of particular interest. Second, external factors. This is related to the globalization process. Globalization necessitates the existence of socio-cultural interaction on a broad scale. In this context, Islam as the order of the order value is faced with modern values, which at a certain point is not only not in harmony with the values that brought Islam, but also diametrically opposite, so that the radicals tried to respond in the form of denial, even resistance.